Peran Self-Compassion Sebagai Moderator dalam Hubungan Antara Stres dan Prokrastinasi Akademik pada Mahasiswa - Novieta, Novieta (Universitas Negeri Makassar, 2025)
Generation Z students often face high levels of stress due to academic demands, financial concerns, and social pressures. One common response to such stress is academic procrastination—deliberate delay in completing academic tasks, which negatively impacts performance. This study aimed to examine the role of self-compassion as a moderator in the relationship between stress and academic procrastination among university students. The study employed a quantitative correlational approach using Moderated Regression Analysis (MRA). A total of 406 Generation Z students were selected through purposive sampling. Data were collected through online questionnaires measuring stress, self-compassion, and academic procrastination, and analyzed using SPSS version 25. The findings revealed that stress significantly predicted higher levels of academic procrastination. Self-compassion also showed a significant direct effect in reducing procrastination. However, it did not moderate the relationship between stress and academic procrastination. Further analysis found that self-compassion significantly mediated this relationship. In conclusion, while self-compassion does not serve as a moderator, it plays a crucial mediating role in reducing the impact of stress on academic procrastination. These results highlight the importance of promoting self-compassion among students. Educational institutions are encouraged to implement programs such as mindfulness training or stress-management workshops that enhance students' adaptive coping and self-compassion.